(untitled) (Heritage, 2022)
The subject of this paper is the influence of cinema on the creation of the past different from that provided by written history. The goal is to show how films, especially documentaries and war spectacles, have a role to play in creating a desirable history. Revisionism on film is not based on new sources or new knowledge that has been obtained in a scientifically based way, but interpretations that are contrary to established historical facts are loaded with partial and unscientific methods. Using the method of content analysis, we will present the topic through, two Kosovo, one Croatian and one French film, of different genres, created in the second decade of the 21st century.